Question
12. \( \left\{\begin{array}{l}4 x-y=-4 \\ 5 x=2 y+1\end{array}\right. \)
Ask by Curry Chambers. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The solution to the system of equations is \( x = -3 \) and \( y = -8 \).
Solution
To solve the system of equations:
\[
\begin{cases}
4x - y = -4 \quad \text{(1)} \\
5x = 2y + 1 \quad \text{(2)}
\end{cases}
\]
**Step 1: Express \( y \) in terms of \( x \) from Equation (1).**
\[
4x - y = -4 \\
\Rightarrow y = 4x + 4 \quad \text{(3)}
\]
**Step 2: Substitute Equation (3) into Equation (2).**
\[
5x = 2y + 1 \\
5x = 2(4x + 4) + 1 \\
5x = 8x + 8 + 1 \\
5x = 8x + 9
\]
**Step 3: Solve for \( x \).**
\[
5x - 8x = 9 \\
-3x = 9 \\
x = -3
\]
**Step 4: Substitute \( x = -3 \) back into Equation (3) to find \( y \).**
\[
y = 4(-3) + 4 \\
y = -12 + 4 \\
y = -8
\]
**Solution:**
\[
x = -3, \quad y = -8
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To solve the system of equations, we can rearrange the first equation for \( y \): From \( 4x - y = -4 \), we get \( y = 4x + 4 \). Now, we can substitute this expression for \( y \) into the second equation: \( 5x = 2(4x + 4) + 1 \). Simplifying gives us \( 5x = 8x + 8 + 1 \), leading to \( 5x = 8x + 9 \), which can be rewritten as \( 5x - 8x = 9 \). Therefore, we find \( -3x = 9 \) or \( x = -3 \). Now, substituting \( x = -3 \) back into the expression for \( y \): \( y = 4(-3) + 4 = -12 + 4 = -8 \). Thus, the solution to the system is \( (x, y) = (-3, -8) \).